2020
DOI: 10.1039/c9ob02397f
|View full text |Cite
|
Sign up to set email alerts
|

ortho-Substituted lipidated Brartemicin derivative shows promising Mincle-mediated adjuvant activity

Abstract: Structure activity relationship studies of lipidated Brartemicin analogues have revealed the potent adjuvant activity of ortho-substituted Brartemicin analogue 5a, which was better than that of p-OC18 (5c) and C18dMeBrar (4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Brartemicin, a glycosyl glycoside derivative isolated from Nonomuraea species with similarity in structure to TDB, was originally identified for its antitumor activities and is also recognized by Mincle [ 109 , 115 ]. Lipidated Brartemicin analogues and especially the o ‐substituted variant showed strong inflammatory activities, inducing Mincle signaling and pro‐inflammatory cytokine responses in both mouse bone marrow‐derived macrophages and human monocytes [ 116 , 117 ].…”
Section: New Glyco‐based Strategies To Steer Immune Responses In Infection Cancer and Autoimmunitymentioning
confidence: 99%
“…Brartemicin, a glycosyl glycoside derivative isolated from Nonomuraea species with similarity in structure to TDB, was originally identified for its antitumor activities and is also recognized by Mincle [ 109 , 115 ]. Lipidated Brartemicin analogues and especially the o ‐substituted variant showed strong inflammatory activities, inducing Mincle signaling and pro‐inflammatory cytokine responses in both mouse bone marrow‐derived macrophages and human monocytes [ 116 , 117 ].…”
Section: New Glyco‐based Strategies To Steer Immune Responses In Infection Cancer and Autoimmunitymentioning
confidence: 99%
“…C 8 GlcC 8 This work builds on related efforts exploring structure activity relationships of acyl-hexoses (as analogues of glucose monomycolate), 15,16 glycosyloxy-stearates (as analogues of the mannosyloxymannitol glycolipid from Malassezia pachydermatis), 28 glycerolipids (as analogues of glycerol monomycolate), 27,29 mono- 13 and diacyl trehaloses, 12,30 and lipidated diaroyltrehaloses (as analogues of brartemicin). 14,31 The present work is notable for the simplicity of the resulting agonists and the fact that unlike acyl-hexoses they exist as single stereoisomers.…”
Section: Nfat-gfp (%)mentioning
confidence: 99%
“…[3] Notably, TDB has been applied to a cationic liposomal system CAF01, [8] which was evaluated in human clinical trials against tuberculosis and HIV. [9,10] Various Mincle ligands have been reported including the glycolipids such as 6-acylated glycosides, [11] glucosyl diacylglycerides, [12][13][14] other trehalose esters, [15][16][17][18][19][20][21][22][23][24] and also recently found cholesteryl acyl α-glucosides (αCAG). [25][26][27] We previously reported that 1-monoacylglycerol harbors relationships between activity and acyl chain length.…”
Section: Introductionmentioning
confidence: 99%